The Effectiveness of Psychoeducation as A Preventive Effort in Reducing Bullying Behavior at SMP Muhammadiyah 8 Surakarta - Mutiarawati, Wanda; Muntazah, Nurul; Karyani, Usmi (Universitas Muhammadiyah Surakarta, 2025)
The increasing prevalence of bullying among junior high school students has become a pressing concern worldwide, impacting various aspects of students' lives and educational environments. This study investigates the effectiveness of psychoeducational intervention as a preventive measure to reduce bullying behavior at SMP Muhammadiyah 8 Surakarta. Bullying, which manifests in physical, verbal, social, emotional, and cyber forms, poses serious risks to victims and negatively affects school communities. The high incidence rates, particularly in Indonesia the highest in ASEAN—underscore the urgency of implementing effective prevention strategies. Initial assessment identified bullying as the predominant issue affecting student welfare and school climate, driven largely by social conflicts and peer dynamics. Victims often suffer long-term psychological consequences such as depression, post-traumatic stress disorder, and diminished psychological well-being. The study highlights the interconnected impact of bullying on both victims and perpetrators, underscoring the importance of early and effective interventions.The psychoeducational program implemented in this research comprises five stages: assessment, preparation, implementation, evaluation, and follow-up. The study involved a population of 523 students, with a purposive sample of 48 students from two classes—regular 7A and IT class 8-1. Data collection included pre- and post-tests and interviews, with analyses conducted using nonparametric Wilcoxon Signed-Rank tests and paired sample t-tests to determine changes in knowledge and awareness about bullying before and after the intervention. Results demonstrated a significant improvement in students' understanding of bullying-related materials after participation in the psychoeducational sessions. Pre-test mean scores (M=7.04; SD=1.71) increased notably in the post-test (M=8.33; SD=1.49) (p=0.001 < 0.05), evidencing the program's effectiveness in enhancing knowledge and preventive attitudes toward bullying. Comprehensive content covered the nature and forms of bullying, its impact on victims and aggressors, and practical prevention strategies emphasizing empathy, tolerance, self-protection, and reporting mechanisms. Engaging delivery methods—including interactive discussions and creative activities like poster-making both manually and digitally—encouraged active student participation and reinforced the program's messages.The psychoeducational approach not only imparted vital knowledge but also fostered social skills, such as empathy, effective communication, and respect, which are critical to sustaining a safe and supportive school environment. The involvement of students in creating anti-bullying posters and slogans amplified their sense of ownership and responsibility toward fostering a bully-free culture. Evaluation feedback from participants indicated strong agreement on the program's clarity, delivery, and usefulness in increasing awareness and reducing bullying tendencies. Follow-up activities included displaying student-created posters in areas prone to bullying and gathering additional feedback, which reflected increased student commitment to counteract bullying behaviors. The findings align with prior research corroborating the positive influence of psychoeducation on reducing bullying and promoting safer school environments. Psychoeducation, especially when coupled with participatory and creative elements, shows great promise as a scalable and practical intervention for bullying prevention programs within educational settings.In conclusion, psychoeducation proves to be an effective strategy for preventing bullying in junior high schools by significantly improving students' knowledge, awareness, and preventive behaviors. Integrating this approach into school programs can contribute to the development of inclusive, respectful, and safe learning environments where bullying is actively discouraged and addressed. The study recommends broader adoption and continuous refinement of psychoeducational interventions to sustain positive behavioral and cultural change in schools.